Ekspresi Visual Memori Traumatik - Florenza Octarina; Ariesa Pandanwangi; Belinda Sukapura Dewi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
An accident experienced by a person, becomes an unforgettable experience. Events that are embedded in memory are often a source of inspiration for artists in the creative process. Some great artists who have experienced an accident have become ideas in the process of creation. The purpose of this creation is to visualize an accident that is recorded in memory and leaves a deep trauma, so that emotions and expressions through art can be appreciated by appreciators. The method used is descriptive analysis and historical. The results of the creation of the artwork are 4 works of art using oil paint on canvas measuring 100 x 120 cm which carry trauma, through these artworks the appreciators can feel the emotions offered by the artist. The visualization in this work is the object of the human body gesture which is dominated by a centered or centered composition with black, white, and gray monochrome colors.Peristiwa kecelakaan yang dialami oleh seseorang, menjadi sebuah pengalaman yang tak terlupakan. Peristiwa yang melekat dalam ingatan kerap menjadi sumber inspirasi seniman dalam proses kreatif. Beberapa seniman besar yang pernah mengalami sebuah sebuah peristiwa kecelakaan, justru menjadi gagasan dalam proses penciptaan. Tujuan penciptaan ini untuk memvisualisasikan sebuah peristiwa kecelakaan yang terekam dalam memori dan meninggalkan trauma yang mendalam, sehingga emosi dan ekspresi melalui karya seni dapat diapresiasi oleh apresiator. Metode yang digunakan adalah deskriptif analisis/historis. Hasil dari penciptaan karya seni adalah 4 karya seni dengan menggunakan cat minyak diatas kanvas berukuran 100 x 120 cm yang mengusung traumatis, melalui karya seni tersebut para apresiator mampu merasakan emosi yang ditawarkan oleh seniman. Visualisasi dalam karya ini adalah objek gesture tubuh manusia yang didominasi dengan kmposisi memusat atau ditengah dengan warna monokrom hitam, putih, abu-abu.